Destination Climate Adaptation. (February 2019) - Čavlek, Nevenka; Cooper, Chris; Krajinović, Vanja; Srnec, Lidija; Zaninović, Ksenija
A key element in the product mix of destinations is climate. Climate represents a critical part of a destination's economic and resource base such that changes in climate will trigger human responses in terms of demand and the type of activities that the climate will support. This threatens the competitiveness, sustainability, and economic viability of destinations. This research note focuses on destination adaptation to climate change that is anticipatory not reactive, based on projecting future climate scenarios for a destination and then assessing the tourism products that the future climate will support. It outlines an original data-driven approach to adaptation that is generalizable to other destinations. The research note describes an exploratory research collaboration in Croatia between tourism and climate scientists that allows, first, the modeling of a destination's projected climate conditions and, second, the products and activities that can be supported by these climate scenarios using climate indices for tourism.